Ali A. Mazrui, IIIT, and the Muslim Experience in the United States of America (American Journal of Islam and Society, 2015)
This editorial is dedicated to paying a tribute to Professor Ali A. Mazrui, whopassed away in Binghamton, New York, on October 13, 2014. From 2009(AJISS 26:1) until his passing, Professor Mazrui was the editor-in-chief forthis journal. In years to come, we may consider dedicating a special issue tohim and his general intellectual contributions. But for now, we present the followingtribute penned by his friend and colleague, Professor Sulayman S.Nyang (Howard University, Washington, DC), as published in IIIT “SpecialIssue: Farewell Professor Ali Mazrui” (October 2014).Professor Ali A. Mazrui, the celebrated scholar, author, and public intellectualfrom Kenya came, performed, and departed gracefully. Certainly, those whoknew him well gladly fared him well, knowing beyond reasonable doubt thathe had the nerve and the verve to represent both Islam and Africa faithfullyand effectively. It is against this background that one can examine a profile ofthe man and his legacies within many domains in America, the Islamic world,and in the larger world ...